Design process of patient-specific osteosynthesis plates using topology optimization. Issue 5 (2nd September 2021) - Park, Si-Myung; Park, Soyeon; Park, Jieun; Choi, Minwook; Kim, Laehyun; Noh, Gunwoo
Abstract: To reduce complications related to the osteosynthesis plating system, the use of a patient-specific plate design was proposed. However, the issue of associated complications is still critical. Because existing patient-specific plate designs have mainly relied on parametric studies, a design method is needed that considers the complex factors influencing the performance of the reconstruction and that can be generalized for various patients. The goal of this study was to propose a design process that can strengthen the advantages of a customized plate to reduce patient discomfort and ensure the stability of surgery. We applied topology optimization to design a plate for a case of mandibular condyle fracture. The optimization problem was set to maximize the plate stiffness and minimize its volume. The performance of the designed plate was evaluated using finite element simulations, which approximated the various mastication states. Plate performance was then compared with the performance of two conventional plating systems: bent plates and computerized numerical control-machined plates. The conventional plate models used a pair of mini-plates, and the bent plate was modeled by conducting bending simulation. Each finite element model was appraised via masticatory simulations under static molar-jaw-closing conditions. Differences in stress concentration were noted between the model with bent plates and the model with computerized numerical control-machined plates. The most severe stress concentration occurred in the bent plate, which was affected by the residual stress from the bending process. In comparison with the two conventional plates, the newly designed plate exhibited significantly improved biomechanical stability in terms of stress and stiffness and had approximately twice the endurance capability against fractured bone separation. The newly designed plate was designed to have a balance between volume and plate stiffness, and it showed superior stability over the conventional plates. The proposed plate design process using topology optimization is an effective method not only because it enhances the advantages of the patient-specific plate but also because it can be applied in various reconstruction cases. Graphical Abstract: